Meningkatkan Kualitas Pembelajaran Parasitologi: Keberhasilan Kelas Kolaborasi Praktisi Mengajar dalam Mengembangkan Kompetensi Mahasiswa IKIP Budi Utomo - Qomariyah, Ismi Nurul; Hindun, Nurmala (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2023)
This research explores the potential for a collaborative approach between parasitology practitioners and Budi Utomo Teacher Training and Education Institute (IKIP) students in improving parasitology education. The background of this research arises from the urgent need to develop student competence in understanding the increasingly complex and diverse world of parasitology. The purpose of this study is to identify the effectiveness of collaborative classroom teaching practitioners in increasing students' understanding of the basic concepts of parasitology and developing their practical skills. This research method involves the development of a collaborative curriculum and the implementation of structured teaching practices involving teachers, practitioners, and students simultaneously. The results showed significant improvements in students' understanding of parasitic nature, life cycles, and control strategies. In addition, direct interaction with practitioners provides deep insight into the practical application of theory in real-world situations. The study provides strong evidence that collaborative classroom teaching practitioners can enhance the effectiveness of parasitology education, enrich students' learning experiences, and prepare them with skills relevant for industry or future research. These findings provide a foundation for the development of innovative teaching methods in parasitology education and are suggested for adoption in various higher education institutions.